2013
DOI: 10.1128/jvi.03262-12
|View full text |Cite
|
Sign up to set email alerts
|

Role of DNA Methylation in Expression and Transmission of Porcine Endogenous Retroviruses

Abstract: c Porcine endogenous retroviruses (PERV) represent a major safety concern in pig-to-human xenotransplantation. To date, no PERV infection of a xenograft recipient has been recorded; however, PERVs are transmissible to human cells in vitro. Some recombinants of the A and C PERV subgroups are particularly efficient in infection and replication in human cells. Transcription of PERVs has been described in most pig cells, but their sequence and insertion polymorphism in the pig genome impede identification of trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…After embryonic development, they are strictly repressed and become permanently silenced 8, 9. Several studies have demonstrated that DNA methylation plays a crucial role in such timing and long-lasting control in silencing HERVs 10, 11, 12, 13, 14…”
Section: Introductionmentioning
confidence: 99%
“…After embryonic development, they are strictly repressed and become permanently silenced 8, 9. Several studies have demonstrated that DNA methylation plays a crucial role in such timing and long-lasting control in silencing HERVs 10, 11, 12, 13, 14…”
Section: Introductionmentioning
confidence: 99%
“…Matouskováatt. al found that 5′long terminal repeats (LTRs) of PERV amplified from PK15 contained 2.7% methylated CpG and no specific patterns of CpG methylation were observed in PERV 5′LTR sequences [39]. These results suggest minor methylation variation in PERV 5′LTR in PK15.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers suggested that DNA hypomethylation is involved in porcine endogenous retrovirus (PERV) activation [39]. PK15 cell lines have been shown to be positive for PERV.…”
Section: Discussionmentioning
confidence: 99%
“…Methods have been developed to screen for the absence of intact genomic PERV‐C env sequences (hereafter referred to as “PERV‐C negative”), which due to sequence variations require multiple assays as well as the PERV mRNA expression levels , allowing for the potential selection of donor animals and porcine islet products. Methods being developed in the field of epigenomics promise to illuminate the role of epigenetic transcriptional silencing of retrovirus and PERV expression . The appropriate role of the PERV infectivity assay which entails the long‐term in vitro coculture of islet product or surrogate donor cells with susceptible human cells for the assessment of PERV infectivity potential remains uncertain.…”
Section: New and Underappreciated Topics Not Addressed In The Originamentioning
confidence: 99%